2020
DOI: 10.1002/hep.31223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mandatory 6‐Month Waiting Period on Waitlist and Transplant Outcomes in Patients With Hepatocellular Carcinoma

Abstract: BaCKgRoUND aND aIMS: Organ Procurement and Transplantation Network/United Network for Organ Sharing (OPTN/UNOS) policy mandates a 6-month waiting period before exception scores are granted to liver transplant candidates with hepatocellular carcinoma (HCC). This study aims to evaluate waitlist and posttransplant outcomes in patients with HCC, before and after implementation of the 6-month waiting rule. appRoaCH aND ReSUltS: We examined two groups from the UNOS registry: Group 1 (pre-6-month rule) consisted of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Our study expands several recent studies evaluating the impacts of the 2015 HCC exception policy change. 13 15 Ishaque et al showed that the policy resulted in decreased transplantation rates and increased mortality/dropout for HCC candidates, attenuating the advantage they have compared with non-HCC candidates. Brondfield et al demonstrated longer waitlist times, particularly in short-wait regions, and decreased regional variability in dropout rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study expands several recent studies evaluating the impacts of the 2015 HCC exception policy change. 13 15 Ishaque et al showed that the policy resulted in decreased transplantation rates and increased mortality/dropout for HCC candidates, attenuating the advantage they have compared with non-HCC candidates. Brondfield et al demonstrated longer waitlist times, particularly in short-wait regions, and decreased regional variability in dropout rates.…”
Section: Discussionmentioning
confidence: 99%
“…This ensured that all imaging findings were available during candidates’ waiting time but also led to a smaller-sized postpolicy cohort than that reported by other investigators. 13 15 …”
Section: Discussionmentioning
confidence: 99%
“…Patients who received MELD exceptions for hepatocellular carcinoma (HCC) and non‐HCC were separately analyzed and initial MELD‐Na score was included in the risk adjustment. For patients with HCC exception, 180‐day and 1‐year waitlist outcomes were assessed, because of mandatory 6‐month waiting rule before being granted for an exception score [7]. For those with MELD exception for other reasons, 90‐day and 1‐year outcomes were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in regions 1 or 9 of the United States, which have long wait lists, more than 70% of the patients with HCC have been waiting for more than a year to undergo LT 4 . In 2015, UNOS/OPTN policy was modified to mandate a 6‐month delay before patients with HCC are given exception points, making wait times even longer 5 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, in regions 1 or 9 of the United States, which have long wait lists, more than 70% of the patients with HCC have been waiting for more than a year to undergo LT. 4 In 2015, UNOS/OPTN policy was modified to mandate a 6-month delay before patients with HCC are given exception points, making wait times even longer. 5 Locoregional therapies (LRTs) like transarterial chemoembolization (TACE) or ablation are used to prevent tumor progression while waiting on the list. Achieving lower viable tumor burden in the explant has been shown to be associated with lower risk for recurrence.…”
Section: Introductionmentioning
confidence: 99%